Determinación de las necesidades hídricas del cultivo de maíz (Zea Mays), mediante el lisímetro volumetríco, en el sector El Porvenir perteneciente al sistema de riego Campana-Malacatos - Ureña Ordóñez, Gabriela del Cisne (2017)
The research was carried out in the neighborhood "El Porvenir", belonging to Malacatos parish. It is located 19 km from of Loja city, at the coordinates UTM 9'538.792 m North and 698.259 m East, altitude of 1635 m.s.n.m El Porvenir neighborhood has an average temperature of 19.3 ° C and an average annual rainfall of 821.1 mm, according to the data recorded in the automatic climatological station located in the sector, and according to the bioclimatic classification of Ecuador it can be deduced that El Porvenir sector presents a preliminary climatic classification: subtropical-dry. The main objective of this research was: the determination of water needs of the corn crop (Zea mays L.), with the purpose of improving the efficiency of water use; To determine the Evapotranspiration of the reference crop (ETo), through the application of the Penman-Monteith method, to determine the Evapotranspiration of the corn (Etc), using Volumetric Lysimeter, and to determine the Coefficient of cultivation (Kc)for the phenological phases of crop maize. The experimental area was of 48 m2, within it were installed lysimeters of 1 m2 each area. For the cultivation was used the maize variety known as Tusilla, the distance of planting between rows of 1m and between plants of 25 cm. Were sown three grains per shot and was performed a raleo when the plants reached 30 cm in height, giving a density of 4 plants / m2. Of the results obtained, the reference evapotranspiration (ETo) calculated with the Penman-Monteith formula inserted in the Cropwat program, yields the maximum values of 4.69 mm / day for the germination phase, mean of 4.32 mm / day and the lowest Value of 4.07 mm / day in the development phase of the fruit. While the crop evapotranspiration (ETc), determined through the volumetric lysimeter, the highest value was 4.21 mm / day in the development phase of the fruit, middle of 3.45 mm / day and the lowest value in the germination phase of 2.98 mm / day. The values of the coefficient (Kc) for the maize crop calculated by the formula for each phenological phase were: germination 0.64, vegetative development 0.80, fruit development 1.07 and crop 0.77, the values present an increase according to the vegetative development until the fruit development the crop requires greater water need then decreases in the last phase denominated as the harvest. The Phenological phases were: Germination (8 days), vegetative development (53 days), fruit development (35 days) and harvest (21 days); For a total cycle of 117 days. Finally, in the present investigation was determined the total water requirement for the entire vegetative period of cultivation, being 422.22 mm, which corresponds to 4,222.2 m3 / ha, and 4'222,200 lt / ha, the yield determined per hectare has a value of 7.21tn or 7,207.50 kg. The relation water consumption / performance is of 585.81 liters, that is to say, that to obtain a kilogram of maize requires 585.81 liters of water. The estimation of the water requirement of the crops is considered a fundamental part for the design, construction, installation and operation of any irrigation system. Key words: Water requirement, Reference evapotranspiration, Crop evapotranspiration, Crop coefficient (Kc), volumetric lysimeter.